A (im)possibilidade da execução provisória da pena: uma análise do princípio constitucional da presunção de inocência - Almeida, Gustavo Shimabuco Rodrigues de (2017)
The present work, through the dialectical methodology, aims to study the possibility of provisional execution of the sentence, from the point of view of the constitutional principle of the presumption of innocence, present in art. 5 of CF / 88. At the outset, there is in the Code of Criminal Procedure, which was created in 1941 during an authoritarian regime, the presence of art. 637 that establishes the absence of suspensive effect in extraordinary appeals. Thus, the understanding applied before the Federal Constitution of 1988 was about the possibility of executing the sentence provisionally. But with the advent of CF / 88 (constitution more protective of individual rights and guarantees), it became debatable, since the constitution in its art. 5th. LVII, expressly brought the need for a final decision to enable enforcement. Thus, Habeas Corpus petitions began to be filed in extraordinary instances to suspend execution until it became unappealable, since in theory they were illegal prisons. However, even with the constitution requiring a res judicata to execute the sentence, the first understanding of the Federal Supreme Court, in HC 68.726 of 1991, was that there would be no need for a final and unappealable decision, it would only require the exhaustion of the ordinary courts. Such understanding lasted until 2009, when HC 84,078 was judged, which established that it could only execute the sentence after the final sentence of condemnatory criminal sentence, with the exception of cases of precautionary prisons. With this understanding, the constitutional guarantee of the presumption of innocence, as set forth in the 1988 Constitution, was finally observed. However, even without significant changes in the normative instruments, the STF, during the trial of HC 126,292 of 2016, changed its position again , going back to the possibility of provisional execution of the sentence. Therefore, it is noted that the provisional execution in Brazil is an institute devoid of legal certainty, since, on several occasions, the understanding of its constitutionality has changed.